PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN PEMERINGKAT CGPI PERIODE TAHUN 2018 – 2021): PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Devina, Bernadetta; Jacobus Widiatmoko; MG. Kentris Indarti (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This study aims to determine the effect of Corporate Social Responsibility and Corporate Governance with leverage, profitability, and firm size as control variables on firm value. Corporate Social Responsibility is measured by GRI G.4 for 2018-2020 and GRI Standard for 2021. Corporate Governance is proxied by the Corporate Governance Perception Index (CGPI) score. Sampling used a purposive sampling method and produced 100 selected samples. The data in this research is in the form of secondary data taken from the annual financial reports of companies listed in the CGPI rating for the period 2018 – 2021. Data analysis using descriptive analysis and multiple linear regression analysis with the results of the research show Corporate Governance has a positive and significant effect on firm value, while Corporate Social Responsibility has no effect on firm value. Tests on the control variable leverage have a positive and significant effect, while profitability and firm size have a positive but not significant effect on firm value.Keywords: Firm Value, Corporate Social Responsibility, Corporate Governance, CGPI, Leverage, Profitability, Firm Size